PELAKSANAAN NIKAH DAN CERAI DUSUN DI KECAMATAN SIULAK KABUPATEN KERINCI - Yulisa, Ike; Firdaus, Firdaus (Jurnal AL-AHKAM, 2020)
This thesis is entitled the implementation of  nikah and cerai dusun in the sub-district of Siulak district, Kerinci. Kerinci Regency who are married and divorced from the hamlet. This is not in accordance with the provisions of Law No. 1 of 1974 and KHI. Marriage and divorce of the hamlet is carried out involving local teganai. This type of research is field research with a qualitative approach, data analysis in this study by means of descriptive analysis.The results of this study is the implementation of the dusun marriage in Siulak Subdistrict is: the couple who will carry out the dusun marriage inform their willingness to the chief assistant in the local village; the head assistant conveyed the matter to the village head and teganai; the the hamlet pays customary fees, the implementation of the marriage contract. The hamlet divorce implementation in Siulak Subdistrict is: First, those who want to divorce invite traditional leaders or figures. Second, the hamlet divorce process is known as sitting teganai. The cause of  nikah dusun is due to economic, education, lack of religious knowledge, environment and etc. The causes of divorce are due to economic factors, education, a long divorce process and etc.